2011
DOI: 10.1021/ma201728a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of exo-Olefin Terminated Polyisobutylene by Sulfide/Base Quenching of Living Polyisobutylene

Abstract: exo-Olefin (methyl vinylidene)-terminated polyisobutylene (PIB) was synthesized in one pot by quenching TiCl4-catalyzed living PIB with a dialkyl (or) diaryl sulfide at −60 to −40 °C, followed by addition of a base (e.g., triethylamine), followed by warming of the reaction mixture to −20 to −10 °C and final termination with methanol. The initiator was 2-chloro-2,4,4-trimethylpentane (TMPCl); the solvent system was 60/40 hexane/methyl chloride, and 2,6-lutidine was used as a nucleophilic additive during polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…The original approach toward exo ‐olefin PIB involved reaction of tert ‐chloride‐terminated PIB with t BuOK in refluxing THF or EtOK in refluxing THF/EtOH; however, this approach is inconvenient due to long reaction times and the inevitable formation of a small amount of the endo ‐olefin . More recently, quantitative exo ‐olefin‐terminated PIB has been synthesized by direct “end‐quenching” of living carbocationic PIB chain ends via addition reaction with methallyltrimethylsilane or elimination reactions induced by hindered bases, alkoxysilanes, alkyl ethers, or alkyl sulfides . End‐quenching has also allowed for the direct functionalization of living PIB with functional groups other than exo ‐olefin, using quencher molecules of several characteristic types including olefins that add only once to the chain, alkoxybenzenes, and heterocyclic aromatics .…”
Section: Introductionmentioning
confidence: 99%
“…The original approach toward exo ‐olefin PIB involved reaction of tert ‐chloride‐terminated PIB with t BuOK in refluxing THF or EtOK in refluxing THF/EtOH; however, this approach is inconvenient due to long reaction times and the inevitable formation of a small amount of the endo ‐olefin . More recently, quantitative exo ‐olefin‐terminated PIB has been synthesized by direct “end‐quenching” of living carbocationic PIB chain ends via addition reaction with methallyltrimethylsilane or elimination reactions induced by hindered bases, alkoxysilanes, alkyl ethers, or alkyl sulfides . End‐quenching has also allowed for the direct functionalization of living PIB with functional groups other than exo ‐olefin, using quencher molecules of several characteristic types including olefins that add only once to the chain, alkoxybenzenes, and heterocyclic aromatics .…”
Section: Introductionmentioning
confidence: 99%
“…The exo‐olefin terminated PIB is also referred to as “highly reactive” PIB (HR PIB), since it readily reacts with maleic anhydride in a thermal “ene” reaction to produce PIB succinic anhydride that can be converted to polyisobutenylsuccinimide, used as ashless dispersants. In the recent years, several research groups have reported on new catalyst systems for the synthesis of HR PIB . Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application .…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, several research groups have reported on new catalyst systems for the synthesis of HR PIB. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application. [26][27][28] Recently, we reported an ethylaluminum dichloride (EADC)Ábis(2-chloroethyl) ether (CEE) complex as a fully hydrocarbon soluble catalyst that in conjunction with tert-butyl chloride (t-BuCl) initiator in hexanes at 0-20 8C gave HR PIB with quantitative yields and up to 92% exo-olefin end-functionality.…”
mentioning
confidence: 99%
“…HRPIBs synthesis by process (B) could also be conducted via specific termination reaction after completion of living cationic polymerization coinitiated with TiCl 4 by addition of allyltrimethylsilane, strong hindered bases, such as 2,5-disubstituted pyrroles, hindered aliphatic tertiary amines, partially hindered pyridines or sulfides, or modification from tert-chloro-terminated functional PIB chains reaction. [63][64][65][66][67][68][69][70][71][72][73][74][75] The TMPCl/FeCl 3 /iPrOH initiating system has been recently developed in our research group to achieve living cationic polymerization of IB in CH 2 Cl 2 /hexane mixture at 280 C. 19 Very interestingly, the chain-transfer-dominated cationic polymerization of IB with H 2 O/FeCl 3 /iPrOH initiating system in nonpolar hydrocarbons at 240 to 20 C has also been achieved in our research group, leading to direct synthesis of HRPIBs with more than 90 mol % of exo-olefin. 62 It indicates that living cationic polymerization of IB co-initiated by FeCl 3 could be transformed to chain-transfer-dominated process by changing reaction conditions.…”
Section: Introductionmentioning
confidence: 99%